Prolactin Protects Against the Methamphetamine-Induced Cerebral Vascular Toxicity - Rosas-Hernandez, Hector; Cuevas, Elvis; M. Lantz-M Peak, Susan; F. Ali, Syed; Gonzalez, Carmen (Current Neurovascular Research, 2013)
Methamphetamine (Meth) is a highly addictive drug of abuse which alters the dopaminergic system and damages the blood-brain barrier (BBB), structure that protects the brain tissue from the circulating substances in the blood, keeping a low permeability through the presence of tight junctions (TJs) between endothelial cells. Meth increases BBB permeability by decreasing the TJs proteins claudin-5 and occludin and by decreasing the viability of endothelial cells. Individuals abused of Meth have increased blood concentrations of prolactin (PRL); hormone related with milk production, but able to increase the expression of TJs proteins and to decrease permeability on the mammary epithelium and brain endothelial cells. However, the effects of PRL on the permeability of the BBB in the presence of Meth have not been studied. Here, we report Meth-induced apoptosis and decreased cellular proliferation as well as the trans-endothelial electrical resistance (TEER), related to a decrease of claudin-5 and occludin in primary cultured bovine brain microvessel endothelial cells. The expression of the PRL receptor was not altered. Administration of PRL prevented a decrease in cellular proliferation, an increase in apoptosis and restored the TEER and TJs proteins to basal levels. This protection was absent at high Meth concentrations. These data suggest that PRL protects brain endothelial cells against the Meth-induced toxicity. Further investigation is required to study the mechanisms involved and to confirm these effects in vivo.
Keywords: trans-endothelial electrical resistance